Automated drug detection and location identification for visually impaired using image processing and voice commands - Roy, Utshab; Rahman, Md. Ashikur; Hasan, Faysal Bin (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.